2005
DOI: 10.1139/f05-170
|View full text |Cite
|
Sign up to set email alerts
|

Paleolimnology of a fluvial lake downstream of Lake Superior and the industrialized region of Sault Saint Marie

Abstract: A paleolimnological study was undertaken to describe the past environment of the St. Mary's River downstream of Lake Superior. Two sediment cores were obtained from the deepest part of Lake George, a fluvial lake in the river system. Rigorous analyses of radionuclides (210Pb, 226Ra, and 137Cs) and chemical properties provided an accurate sediment chronology. More than 450 diatom species from 47 genera were identified. Diatom and geochemical data indicated gradual environmental change in response to anthropogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…That the unique TP effect is lower than total is due to redundancies, such as correlation to variables like chlorophyll a and turbidity (Figure 1). While it is difficult to confirm the relative importance of these variance partitioning values, the unique variance explained by TP surpasses that observed for TP training sets developed in Europe [46] and Minnesota [47], [48]; 3.9% and 2.5% respectively, as presented by Juggins et al [22]. Of the selected variables, TP independently explained the most variation in the assemblage data, in contrast to alkalinity and chloride which had more than 70% reduction from total to uniquely explained variance.…”
Section: Resultsmentioning
confidence: 99%
“…That the unique TP effect is lower than total is due to redundancies, such as correlation to variables like chlorophyll a and turbidity (Figure 1). While it is difficult to confirm the relative importance of these variance partitioning values, the unique variance explained by TP surpasses that observed for TP training sets developed in Europe [46] and Minnesota [47], [48]; 3.9% and 2.5% respectively, as presented by Juggins et al [22]. Of the selected variables, TP independently explained the most variation in the assemblage data, in contrast to alkalinity and chloride which had more than 70% reduction from total to uniquely explained variance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that in sites with lower contamination, other perturbations (e.g. eutrophication) can override the signal of the effects of the metal/s 52 , 53 . However, within the post-mining period, the most significant changes in the diatom community were caused by the mine-derived salinity increase rather than the increase in toxic metal concentrations per se .…”
Section: Discussionmentioning
confidence: 99%
“…In their core of western Lake Superior, they found stable concentrations of Na up to 1955 ending with an increase in concentration likely resulting from urban inputs in the vicinity of Duluth, Minnesota. Reavie et al (2005) found that Na concentrations gradually increased in the 1800s with European settlement in their core from Lake George, just downgradient from Lake Superior. Sgro and Reavie (2017) attributed Na in their cores in Lake Erie to road salt impacts and found the highest concentrations in surface sediments.…”
Section: Sodiummentioning
confidence: 99%
“…The majority of 137 Cs in surface waters in North America, including the Great Lakes, is due to nuclear weapons testing, which began in 1952 and ended in 1963 with the Limited Test Ban Treaty. In the Great Lakes, the maximum deposition of 137 Cs was in the spring of 1963, though peaks in the sediment may be as much as two years later (ASTDR, 2004a;Reavie et al, 2005). The radionuclide is strongly bound to expandable lattice clay minerals such as illite in the Great Lakes, so it tends to be a reliable temporal indicator in sediment profiles.…”
Section: Cesiummentioning
confidence: 99%